Analysis of the status-quo of the Tertiary education in the Republic of Kazakhstan - Utebayeva, A. B. (Journal of Economic Research & Business Administration, 2016)
Improving of tertiary education connected to implementation of Kazakhstan into the world educational space. The importance of education system from school to university is proved by scientific research carried out by the World Bank, as they have a direct impact on the economic development of the country. The basis of knowledge based modern economic development is tertiary education, which in the framework of Kazakhstan’s educational system consists from technical and vocational education, higher education and post-graduate education. Tertiary education contributes to the creation of intellectual potential, which is the basis for production and use of knowledge, as well as for the implementation of lifelong learning teaching practices. In the article the author explores the current state of tertiary education in Kazakhstan: technical and vocational education and higher education. It reveals a number of problematic issues and proposals of their solution; it also determines the positions of Kazakhstan in the sphere of education in the international rankings.The author considers the functioning conditions and features of world-class universities, it needs the implementation of such experience in the activity of national universities.